Uncertainty and Foreign Direct Investment: A Case of Agriculture in Nigeria - Ajuwon, O. S.; Ogwumike, F. O. (Mediterranean Journal of Social Sciences, 2013)
Premised on economic uncertainty and political instability indicators, this paper examined the role of uncertainty as theyaffected the inflow of FDI into the agricultural subsector of the Nigerian economy given that such empirical work are limited.Employing secondary time series data which spanned 1970 to 2008, on an investment-cointegrated Error Correction Model,this study attempted to fill the gap. Following ADF test for stationarity and a Johenson cointegration test, we found acointegrating relationship among the variables as affirmed by the error correction mechanism parameter. It was revealed thatFDI positively impacted on agriculture not only in the short run but also in the long run. This will also engender domesticincome diversification which will boost agricultural sector and stem the erstwhile neglect of the sector. Further, politicalinstability adversely affected agricultural investments in the long run. An enabling environment should be provided to attractinvestment on short and long term basis. Also exchange rate fluctuation, high lending and inflation rates problems should beaddressed.